1996
DOI: 10.1021/jp953658l
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of Coumarin 480 in Reverse Micelles. Slow Relaxation of Water Molecules

Abstract: The picosecond time-resolved Stokes shift of the laser dye coumarin 480 (I) is studied in Aerosol OT-heptane reverse micelles at various concentrations of water. On addition of water to a n-heptane solution of I containing 0.09 M AOT, the emission spectrum of I exhibits a prominent shoulder at 480 nm which is ascribed to the dye molecules in the water pool of the reverse micelles. In n-heptane, the fluorescence decays of I at short and long wavelengths are identical, which rules out any time-resolved Stokes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
293
3
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(325 citation statements)
references
References 55 publications
26
293
3
3
Order By: Relevance
“…10 One consistent conclusion of their studies is that there is not a one-to-one correspondence between steady-state spectra and the time-dependent Stokes shift function, S(t): ''...steady-state spectroscopy may not always be a good predictor for dynamical behavior.'' 14 Bhattacharyya and co-workers have measured the timedependent fluorescence of the dye molecule, Coumarin 480, in solventless zeolites, 4 aqueous micelles 5 and reverse micelles, 6 in water pools in a sol-gel matrix, 7 and vesicles. 8 They found that the long-time solvation dynamics depend strongly on the environment with a long-time decay of ϳ0.8 ns in the sol-gel matrix, 7 0.6 -2.4 ns in micelles ͑using different surfactants͒, 5 8 -12 ns in reverse micelles, 6 11 ns in vesicles, 8 and ϳ15.4 ns in the solventless zeolites.…”
Section: Experimental Workmentioning
confidence: 99%
See 2 more Smart Citations
“…10 One consistent conclusion of their studies is that there is not a one-to-one correspondence between steady-state spectra and the time-dependent Stokes shift function, S(t): ''...steady-state spectroscopy may not always be a good predictor for dynamical behavior.'' 14 Bhattacharyya and co-workers have measured the timedependent fluorescence of the dye molecule, Coumarin 480, in solventless zeolites, 4 aqueous micelles 5 and reverse micelles, 6 in water pools in a sol-gel matrix, 7 and vesicles. 8 They found that the long-time solvation dynamics depend strongly on the environment with a long-time decay of ϳ0.8 ns in the sol-gel matrix, 7 0.6 -2.4 ns in micelles ͑using different surfactants͒, 5 8 -12 ns in reverse micelles, 6 11 ns in vesicles, 8 and ϳ15.4 ns in the solventless zeolites.…”
Section: Experimental Workmentioning
confidence: 99%
“…14 Bhattacharyya and co-workers have measured the timedependent fluorescence of the dye molecule, Coumarin 480, in solventless zeolites, 4 aqueous micelles 5 and reverse micelles, 6 in water pools in a sol-gel matrix, 7 and vesicles. 8 They found that the long-time solvation dynamics depend strongly on the environment with a long-time decay of ϳ0.8 ns in the sol-gel matrix, 7 0.6 -2.4 ns in micelles ͑using different surfactants͒, 5 8 -12 ns in reverse micelles, 6 11 ns in vesicles, 8 and ϳ15.4 ns in the solventless zeolites. 4 ͑The solvent relaxation dynamics for Coumarin 480 in bulk aqueous solution takes place in 310 fs.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Mid-infrared ultrafast pumpprobe spectroscopy of RMs of different well-defined sizes revealed slow vibrational relaxation dynamics of water at the interface. 16 Using the picosecond-resolved fluorescence spec-…”
Section: Introductionmentioning
confidence: 99%
“…The solvation times in the RTIL pools were found to be nearly independent of [bmim] [BF 4 ] content and size of the microemulsion droplets. By contrast, a decrease in solvation time in aqueous reverse microemulsions with increasing R values has been documented in literature (Sarkar et al, 1996;Riter et al, 1998). Using isothermal titration microcalorimetry Li et al determined the heat of dilution and extracted the second virial coefficient, b 2 of these microemulsions (Li et al, 2008).…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 99%